Law enforcement against criminal acts Transfer of fiduciary guarantee objects Without permission of the fiduciary recipient - Simare Mare, Chandra P; Sidauruk, Jinner (Inspiring Law Journal, 2025)
The purpose of this writing is to find out how the law is enforced against the criminal act of Transferring Fiduciary Security Objects Without the Permission of the Fiduciary Recipient based on Law Number 42 of 1999 concerning Fiduciary Guarantees. By using qualitative research methods, it is concluded that this paper aims to determine the rights of fiduciary recipients regarding fiduciary collateral objects and law enforcement against perpetrators of criminal acts of transferring fiduciary collateral objects without the fiduciary recipient's permission based on Law Number 42 of 1999 concerning Fiduciary Guarantees. Fiduciary is the transfer of ownership rights to an object based on trust. However, in practice, problems are often encountered when transferring collateral without the approval of the fiduciary or creditor, causing the creditor to suffer losses. Transferring the object of a fiduciary guarantee is a criminal act regulated in the applicable legal basis, namely Article 23 paragraph (2) and Article 36 of Law of the Republic of Indonesia Number 42 of 1999 concerning Fiduciary Guarantees. The criminal sanctions given are a maximum imprisonment of 2 (two) years and a maximum fine of Rp. 50,000,000 (Fifty Million Rupiah)